Developmental changes and metabolic reprogramming during establishment of infection and progression of Trypanosoma brucei brucei through its insect host. - Arunasalam Naguleswaran; Paula Fernandes; Shubha Bevkal; Ruth Rehmann; Pamela Nicholson; Isabel Roditi (Public Library of Science (PLoS), 2021)
Trypanosoma brucei ssp., unicellular parasites causing human and animal trypanosomiasis, are transmitted between mammals by tsetse flies. Periodic changes in variant surface glycoproteins (VSG), which form the parasite coat in the mammal, allow them to evade the host immune response. Different isolates of T. brucei show heterogeneity in their repertoires of VSG genes and have single nucleotide polymorphisms and indels that can impact on genome editing. T. brucei brucei EATRO1125 (AnTaR1 serodeme) is an isolate that is used increasingly often because it is pleomorphic in mammals and fly transmissible, two characteristics that have been lost by the most commonly used laboratory stocks. We present a genome assembly of EATRO1125, including contigs for the intermediate chromosomes and minichromosomes that serve as repositories of VSG genes. In addition, de novo transcriptome assemblies were performed using Illumina sequences from tsetse-derived trypanosomes. Reads of 150 bases enabled closely related members of multigene families to be discriminated. This revealed that the transcriptome of midgut-derived parasites is dynamic, starting with the expression of high affinity hexose transporters and glycolytic enzymes and then switching to proline uptake and catabolism. These changes resemble the transition from early to late procyclic forms in culture. Further metabolic reprogramming, including upregulation of tricarboxylic acid cycle enzymes, occurs in the proventriculus. Many transcripts upregulated in the salivary glands encode surface proteins, among them 7 metacyclic VSGs, multiple BARPs and GCS1/HAP2, a marker for gametes. A novel family of transmembrane proteins, containing polythreonine stretches that are predicted to be O-glycosylation sites, was also identified. Finally, RNA-Seq data were used to create an optimised annotation file with 5' and 3' untranslated regions accurately mapped for 9302 genes. We anticipate that this will be of use in identifying transcripts obtained by single cell sequencing technologies.